Impact of tannin as sustainable compatibilizer for wood‐polypropylene composites. Issue 12 (10th July 2017) - Missio, André L.; Mattos, Bruno D.; de Cademartori, Pedro H.G.; Berger, Camila; Magalhães, Washington L.E.; Haselein, Clovis R.; Gatto, Darci A.; Petutschnigg, Alexander; Tondi, Gianluca
Abstract : Wood Plastic Composites (WPCs) are well‐known products which combine the high mechanical properties of wood with the high hydrophobicity and formability of polypropylene (PP). They are largely used for decking, cladding and flooring for outdoor constructions but they still present some drawbacks due to the limited chemical affinity of the two materials. In this paper, the addition of mimosa ( Acacia mearnsii ) tannin as compatibilizer was tested and these composites were characterized via SEM, TGA, DSC, DMA, mechanical testing, water absorption and contact angle. The tannin‐containing WPC presented lower interspaces between PP and lignocellulosic matrix, higher hydrophobicity and comparable mechanical performances. These results were due to the high compatibilization effect of the tannin, which allow getting similar results with 15% less lignocellulosic material. The lower crystallinity observed for PP in tannin‐containing composites allowed a better contact between the wooden fractions. Although good physical compatibilization was obtained no evidences of chemical bonding were observed by FT‐IR. The enhanced interphase contact and the higher hydrophobicity registered for the tannin‐containing WPCs suggest that this natural, easily available extract can be a cheap and green additive to enhance the service‐life for outdoor applications. POLYM. COMPOS., 39:4275–4284, 2018. © 2017 Society of Plastics Engineers